Spatiotemporal expression pattern of alpha, beta, and gamma genes during bohv-5 infection - Cagnini, Didier Quevedo; Badial, Peres Ramos; de Oliveira-Filho, José Paes [UNESP]; Borges, Alexandre Secorun [UNESP]; de Araújo, João Pessoa [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
Bovine herpesvirus 5 is an alphaherpesvirus that causes nonsuppurative meningoencephalitis in cattle. This disease occurs naturally in either outbreaks or isolated cases, and exhibits low morbidity and high lethality. Although previous studies elucidated crucial aspects involved in the pathogenesis of the disease, there is a paucity of information regarding the molecular events contributing to infection and replication of BoHV-5. The objective of the present study was to determine the in vitro gene expression pattern of BoHV-5 (e.g., alpha, beta, and gamma genes) and host cells genes (GAPDH and 18S) over time utilizing different quantities of inoculated virus. Three BoHV-5 genes (bICP0, UL9, US4) and one structural bovine cell gene had their expression accessed by real-time PCR. While the expression of BoHV-5 genes increased during the course of infection, GAPDH gene expression decreased in the host cells, evidencing the effect of viral infection on the expression of bovine cell genes. The 18S ribosomal RNA (rRNA) gene was constitutively expressed throughout BoHV-5 infection. Our data clearly demonstrates that GAPDH gene should not be used as a reference gene in studies of BoHV-5 infection because it was influenced by viral infection. However, 18S rRNA was constitutively expressed and, therefore, is recommended for normalization of BoHV-5 infection studies in bovine cells. The expression of viral genes transcripts was not altered by increasing number of viral particles added to the culture. All viral genes included here demonstrated the same expression pattern over time and there was no difference in the expression of viral genes among the various time points. Our data show important differences comparing to classical studies regarding herpesvirus alpha, beta, and gamma genes expression. More research is necessary to improve our understanding about the BoHV-5 biology during infection. Studies employing next-generation sequencing (i.e., RNA-seq), using both in vitro and in vivo models, would be the next logical step to grasp the virus and host cell’s transcriptome changes over the course of infection.
Expressão temporal de genes alfa, beta e gama durante a infecção pelo bohv-5
Keywords: Bovine herpesvirus 5; Molecular biology; Quantitative PCR; Viral gene expression